Plaster Cast Collections from the 1904 Louisiana Purchase Exposition in Context: Examining Culturally Determined Significance through Environment and Time - Disalvo, Lauren (Material Culture Review, 2012)
Through an exploration of the lives of two sets of classical plaster casts that began at the 1904 Louisiana Purchase Exposition in St. Louis, I will track how space, context, and time established the function, specific cultural meanings, and authenticity of these casts. Regardless of the fact that these collections began in a similar environment, they were adapted for different cultural uses and agendas and accrued multiple levels of cultural significance in their movements through different environments and through time.